Ville e palazzi suburbani tra tardo Quattrocento e Cinquecento nel nord ovest dell’Italia tra innovazione e continuità - Beltramo, Silvia (Opus Incertum, 2019)
The renewal policies concerning Medieval castles and noble houses transformed into in palaces and villas, also involve the subAlpine territories. In particular, at the end of the 15th century and the beginning of the 16th, the main noble dynastic families became carriers of new construction practices aimed at the renovation of existing structures and the opening of new construction sites for palaces and villas outside urban centres and in the countryside. The marquises of Saluzzo encouraged the practice of building new residences in a suburban landscape of great relevance: the palace of Revello, La Morra di Castellar and villa Belvedere constitute an overall project of residences, green areas, both gardens and orchards, which reflect humanist concepts and reinterpret some of the architectural themes of the ‘vivere in villa’ widespread in central and northern Italy. Other noble families of the territory such as the Tapparelli di Lagnasco and the Saluzzo della Manta built new country houses in which they introduced some of the themes of ‘all’antica’ building such as loggias, galleries and grotesque decorative systems.